Associations of individual and combined alterations in essential trace metal levels with breast cancer risk: A case-control study in Tanzania - Emmanuel Njale; John A.M. Mahugija; Dativa J. Shilla; Nyimvua S. Mbare (Journal of Trace Elements in Medicine and Biology, 2026)

Plastic debris facilitates the survival of multidrug-resistant bacterial pathogens in an urban agricultural environment - Michael J. Ormsby; Luke Woodford; James J. Mwesiga; Winnie Ernest; Dativa Shilla; Daniel Shilla; Richard S. Quilliam (Environmental Pollution, 2026)

Mitochondrial cytochrome c oxidase I ( COI ) gene sequence analysis reveals genetic connectivity and recent population expansion in Terebralia palustris (Linnaeus, 1767) along the Tanzanian coastline - Zulfa Ismail Shabani; Aneth Bela David; Joseph Stephen Matata; Changoma Marko Fransis; Dativa Joseph; Daniel Abel Shilla; Fulgence Mpenda; Prosper Laurent Mfilinge; James Leonard Lusana (Marine Biology Research, 2026)

Back-shore vegetation as trap for marine plastic pollution, Dar es Salaam, Tanzania - Frederik Oksbjerg Mikkelsen; Thorbjørn Joest Andersen; Christine Ørsted; Amanda Bojer; Desderius Msafiri; Stanley D. Katega; Martine M. Kabezi; Flora Idan Mwasamila; Dativa J. Shilla; Daniel Shilla; Marianne Nylandsted Larsen; Mikkel Fruergaard (Marine Pollution Bulletin, 2025)

Fluconazole resistant pathogenic yeasts isolated from plastic debris on recreational public beaches in West and East Africa - Ayorinde B. Akinbobola; Dativa Joseph Shilla; Daniel A. Shilla; Richard S. Quilliam (Biologia, 2025)
Plastic pollution in the environment becomes rapidly colonised by microbial communities, which often contain human bacterial pathogens. However, there is a lack of information about the interaction of fungal pathogens with plastic debris, particularly in marine environments. This study screened common plastic wastes collected from a range of recreational public and tourist beaches in Nigeria and Tanzania for colonisation by human pathogenic yeasts. Isolates were identified on selective media with confirmation by ITS sequencing. All beaches and all plastic polymer types were colonised by at least one species of human pathogenic yeast, with Candida tropicalis being the most frequently isolated species across both countries. Importantly, most of these pathogenic yeast isolates showed some level of resistance to fluconazole, which in Africa is the most commonly prescribed anti-fungal drug. Therefore, due to the high potential for human skin exposure at beach environments, plastic debris could pose a significant public health risk.

Association between single and mixed exposure to potentially toxic trace metals and the risk of prostate cancer: a case–control study in Tanzania - Emmanuel Njale; Dativa J. Shilla; Nazima Dharsee; John A. M. Mahugija; Nyimvua S. Mbare (Environmental Geochemistry and Health, 2025)

Microplastic pollution in the Thumbprint emperor (Lethrinus harak) from Tanzanian coastal waters: Occurrence, abundance, characterization, and relevance as a monitoring species - Amina Asiya Nchimbi; Daniel Abel Shilla; Charles Mitto Kosore; Dativa Joseph Shilla; Yvonne Shashoua; Christina Sørensen; Farhan R. Khan (Regional Studies in Marine Science, 2024)

Association between exposure to heavy metals and the risk of breast cancer: A case-control study in Tanzania - Emmanuel Njale; John A.M. Mahugija; Dativa J. Shilla; Nazima Dharsee; Nyimvua S. Mbare (Environmental Toxicology and Pharmacology, 2024)

Settling of buoyant microplastic in estuaries: The importance of flocculation - Simon Nyboe Laursen; Mikkel Fruergaard; Maya Shakunt Dodhia; Nicole Rita Posth; Maja Bar Rasmussen; Marianne Nylandsted Larsen; Dativa Shilla; Daniel Shilla; Jane James Kilawe; Hellen Joseph Kizenga; Thorbjørn Joest Andersen (Science of The Total Environment, 2023)

Microplastics in Marine Nearshore Surface Waters of Dar es Salaam and Zanzibar, East Africa - Amina Asiya Nchimbi; Charles Mitto Kosore; Nancy Oduor; Dativa Joseph Shilla; Yvonne Shashoua; Farhan R. Khan; Daniel Abel Shilla (Bulletin of Environmental Contamination and Toxicology, 2022)